Cultural context and its implications for graphic design (Al-Academy, 2022)
dictates the need to study the cultural aspects of the context and the consequent relations between the person and the objective environment surrounding him, as the philosophical understanding of the role of culture has led to the emergence of new theoretical interpretations of design that are organically linked with the development of society, especially that the development of the human environment philosophically and culturally is linked to the philosophical perception of its role in Culture as a precondition for new theoretical interpretations of design.From the above, this problem can be studied by defining the following question (What are the implications of the cultural context in graphic design)?The research included three chapters, the first chapter being the research problem and the need for it, and the aim of the research was (discovering the mechanisms of the cultural context and their use in graphic design), and then the importance of the research. As for the second chapter, it included the theoretical framework and it may consist of two sections, the first is (the cultural context between concept and application) and the second is (the cultural context in graphic design) and then the third chapter (research procedures), as the researcher adopted the descriptive approach as a method of content analysis, based on what resulted From the theoretical framework of indicators, and then the research sample was deliberately chosen, for samples of cultural posters, to achieve the goal of the research, and then the research came out with results and conclusions, including:1- The cultural context in graphic design is one of the most important clues in determining the meaning of the form and directing its connotation, because the language of the form is a social artistic activity whose understanding depends on the understanding of the components of society, including customs, norms, traditions and cultures.2- The use of the cultural context in the design of the poster achieved the depth of belonging and the cultural embodiment of the country to which the designer belongs.